Word wonders via game-based learning - Jaharudin, Nurul Ain Syuhada; Zaini, Hazrati; Abu Bakar, Noor Suriana (College of Computing, Informatics, and Mathematics, 2025)
This project, Word Wonders via Game-Based Learning, addresses the challenges faced by children with dyslexia by developing a 2D game-based learning application. Because of lack of awareness on the clinch between parents and educators, Dyslexia is another condition that is often diagnosed too late. The idea behind this project is that children, aged from 7 to 12, learn better and faster when using Game-Based Learning (GBL), thus needs a fun and interactive environment that is able to assess the skills of reading, spelling and listening. Our application was designed, developed and evaluated using a Waterfall approach. The application was developed using Construct 3, which is a powerful framework for interactive 2D game development, incorporating colorful graphics, an easy-to-use UI, and clear positive reinforcement. These factors are designed to make learning enjoyable and to detect dyslexic tendencies at an early age. The application was created and usability testing was conducted to assess if it was serving the needs of dyslexic children. It was the game-based approach that led to the increase in user engagement and it has been proven to help parents connect with their children about understanding dyslexia better. By using interactive technology, this project demonstrates the possibility for early diagnosis, leading to positive impacts on the education and well-being of dyslexic children. Future enhancements could include incorporating multilanguage support to broaden accessibility and reach a wider audience.